Introducing and Evaluating an E-Learning Platform for Hajj Guide Certification through Community Service Using the System Usability Scale - Aris Rakhmadi; Syarifur Rizal Miftahul Hasan (ABDIMASTEK, 2026)
The rapid advancement of information technology has driven digital transformation across various training and certification activities; however, the Hajj guide certification process is still conducted through fragmented, non-integrated platforms, leading to inefficiencies in material distribution, task management, and participant evaluation. This community service activity aims to evaluate the usability of an e-learning system as a potential digital solution for Hajj guide certification. The implementation method adopts a structured simulation-based approach, including needs assessment, system demonstration, user interaction, and usability evaluation using the System Usability Scale (SUS) involving 23 respondents with relevant certification experience. The results indicate an average SUS score of 71.13, which falls into the “acceptable” category, reflecting an adequate level of usability and suggesting that the system meets fundamental usability requirements. Therefore, the proposed e-learning system shows potential as a digital solution to more structurally support certification processes. However, further improvements in interface design and navigation are necessary to enhance the overall user experience.